Dinamika Keilmuan Islam pada Masa Klasik dan Pertengahan - Fuad, Ahmad Nur; Zuhdi Dh, Achmad (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2024)
This article explores the dynamics of Islamic scholarship in the classical and medieval periods. During this very long period, Islamic scholarship experienced rapid development, especially during the classical period, although in the middle period its development was often considered to have experienced a decline. Types of scholarship grew in line with the dynamics of Muslims in many regions, and their interaction with the intellectual heritage of ancient Greece in areas conquered by Islam. This article argues that the dynamics of Islamic scholarship cannot be separated from politics or power that provides support and patronage to scientists, while emphasizing that even though in the medieval period there was disintegration of Islamic politics, Islamic scholarship still produced significant scientific figures and works.